An Inquiry for Future Direction of Education in South Korea through Critical Pedagogy and Bricolage - Hur, Changsoo (Ammattikasvatuksen aikakauskirja, 2019)
Korean society is currently under the 2017 system. It pursues a society that values democracy, human rights and peace. To that end, the goal is ‘JeokPaeCheongSan’ (rooting out bad practices of the past or liquidating great accumulation of corruption) that Korean society has due to historical reasons. Education is also moving along with these social and political changes. Indeed, education has already been rooted in alternative education for a decade, and it is trying to change the major paradigm. On the other hand, the discussion of the theoretical discourse that can support this paradigm shift is very passive. However, discussions of this discourse can play an important role in eliminating the confusion that may arise due to change, as they can prove the validity of the change and its sustainability. In this article, I suggest critical pedagogy as a theoretical discourse for South Korea’s educational paradigm shift. Critical pedagogy, which seeks a conscious emancipation, offers educational directions for the elimination of corruption. In addition, I am offering the notion of bricolage as a praxis to overcome theoretical limitations and provide a more practical direction. In the article, I discuss the suitability of this inquiry not only to ‘JeokPaeCheongSan’ but also to the development of diverse capabilities, including but not limited to creativity and cooperation, which can also support future changes in society.